O projeto educacional da revista Educação e Sociedade (1978- 1990) - Santos, Andréia Ferreira dos (2020)
This work which is a bibliographic research, aims to understand how the magazine Educação e Sociedade, published continuously since the late 1970s, in the context of the struggles for the new democratization of the country, formulates and disseminates what was called at the time of a “new educational project” to Brazil. This is a bibliographic search carried out in the editorials from one to thirty-five, and it was read through an analysis script. The results of the research show the extent to which the journal's editors are involved in making the field more dynamic by embodying an educational project founded on at least three main points: the first concerns the commitment to the principles of public education geared towards critically oriented training, particularly for workers; the second, the mobilization of educators to engage in the defense of a public, secular and free school, and the third, the concern with the formulation of public educational policies that would make an effectively democratic education possible to exist. These principles would underpin an equally critical formation, centered on democratic values that would break with technicism and economism in education.